TECHNOLOGY FOR DEVELOPING FUTURE SOFTWARE ENGINEERS’ COMPETENCE THROUGH PEDAGOGICAL SOFTWARE TOOLS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores the scientific and methodological foundations of forming professional competence in future software engineers through the use of pedagogical software tools. It analyzes the possibilities of developing students’ professional competencies in a modern educational environment based on individual approaches, cluster strategies, interactive teaching technologies, and digital platforms. The study also examines the integration of programming languages into the educational process, ensuring interdisciplinary connections, and enhancing independent learning.